Gratitude and health: a brief intervention to reduce undergraduate stress - Fitch-Martin, Arissa, author; Steger, Michael, advisor; Dik, Bryan, advisor; Kuk, Linda, committee member; Harman, Jennifer, committee member (Colorado State University. Libraries, 2015)
Undergraduate students experience a significant amount of stress that negatively impacts their physical and mental health as well as their academic performance. Attempts to reduce stress and its detrimental effects on the lives of college students have either fallen short, require considerable effort, are not utilized, or have not been sufficiently evaluated. Instead, undergraduate students often turn to unhealthy ways of dealing with their stress such as excessive alcohol use. This study aimed to address the lack of efficient and efficacious stress management resources available to undergraduate students. Three-hundred and sixteen undergraduate students were assigned to a gratitude-list, objects-list, or no-treatment control condition. The gratitude intervention did not have a significant impact on perceived stress. However, results provided further evidence that there is a relationship between gratitude and perceived stress. The impact of gender-role identity and trait gratitude was also explored. Implications for future research on gratitude and stress as well as gratitude in general are discussed and suggestions for clinical practice are offered.
Keywords: gratitude; college students; stress